Public perception and behavior toward butterfly diversity and benefits in Bandung, West Java, Indonesia - NURULLIA FITRIANI; BUDIAWATI SUPANGKAT; WAWAN HERMAWAN; JOHAN ISKANDAR; MUHAMAD AZAHAR ABAS (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fitriani N, Supangkat B, Hermawan W, Iskandar J, Abas MA. 2025. Public perception and behavior toward butterfly diversity and benefits in Bandung, West Java, Indonesia. Biodiversitas 26: 5089-5108. Butterflies, with their ecological, cultural, and economic benefits, yet public understanding of their roles in Indonesia remains limited. This study assessed community Knowledge, Attitudes, and Behaviors (KAB) toward butterflies in Bandung, West Java, Indonesia. A mixed-method approach was applied through structured and semi-structured interviews with 100 respondents, complemented by butterfly diversity surveys across 31 urban-to-rural transects. The quantitative data were analyzed using Spearman’s rho and Chi-square tests (N: 100, p<0.05), while qualitative interview data were examined through the SAMMSA framework. Butterfly diversity observations were analyzed descriptively. The result showed that knowledge levels were low (32%), moderate (41%), and high (27%). Attitudes were very positive (64%), moderately positive (33%), and negative (3%). Behaviors were largely pro-conservation (89%), with 8% moderately supportive and 3% low. Age (?: 0.285, p: 0.004) and education (?: 0.292, p: 0.003) were found to correlate positively with knowledge, while occupation significantly influenced attitudes (?²: 41.07, p: 0.008, V: 0.453) and behaviors (?²: 37.82, p: 0.019, V: 0.435). Knowledge did not predict behavior, but attitudes strongly did (?: 0.520, p<0.001, ?: 0.48, R²: 0.395). Field sampling recorded 87 species in five families, dominated by Nymphalidae, with kukupu coklat (brown butterflies) representing the largest folk category. The findings indicate that positive attitudes, more than factual knowledge, drive butterfly conservation behavior. Strengthening conservation in urban areas, therefore, requires experiential learning, cultural integration, and curriculum-based education to foster lasting community engagement in biodiversity protection.